Health Education Bagi Kader Tuberculosis (TB) Tentang Pentingnya Pengawas Minum Obat (PMO) Di Desa Kampung Delima Kecamatan Curup Timur - Putra, Exa Mandala; Putra , Anugerah Deskatama; Elinsanse , Cici; Hilintri , Yatri; Atvennia, Maria; Agustin , Wulan Dari; Rohani , Tuti; Azissah , Danur (Universitas Dehasen Bengkulu, 2025)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. This disease is typically transmitted from person to person through the air when an infected individual coughs, sneezes, or talks. According to the WHO in 2022, Indonesia ranked second in the world for the highest number of TB cases, following India, with approximately 700,000 cases reported, representing 10% of global cases. This figure marks the highest achievement in TB detection in Indonesia's history.The increase in TB cases is influenced by patients' behaviors, such as failing to implement transmission prevention measures like practicing cough etiquette by covering their mouths when coughing or sneezing and not spitting in open areas. This lack of preventive behavior is often due to insufficient knowledge among patients regarding prevention methods. A critical aspect of managing TB cases is the Cure Rate. In 2020, there were 3,268 registered and treated cases in Bengkulu Province, but only 1,322 cases (40%) were declared cured. In Rejang Lebong District, 417 treated cases were recorded in the same year, with only 137 cases (33%) achieving recovery.Data from the annual report of Puskesmas Kampung Delima indicates that TB is one of the programs with low achievement rates, with case detection at only 21.62% of a target of 70%, and a treatment success rate of 0%. The low cure rate at Puskesmas Kampung Delima can be attributed to inadequate education for patients about proper medication adherence and a lack of awareness regarding the importance of consistent medication intake.To address these issues, we conducted community service focused on TB by providing health education to TB cadres working within the Puskesmas Kampung Delima area about the significance of medication supervision for TB patients. One cadre from Kampung Delima village has successfully understood and grasped the material presented regarding the importance of Medication Supervisors (PMO). The results from this activity showed an increase in knowledge about the importance of PMO for TB patients among the cadres after health education was conducted.